Regional & Queer: Refusing to be Invisible, Creating queer space in a non-queer world - Akkadia Ford (Cybergeo)
The Queer Fruits Film Festival experience demonstrated that there is a vitality in independent GLBTIQ film culture and an enthusiastic audience waiting to view films which show stories which reflect our lives on screen. Geographic isolation and fewer social and cultural resources, also underscore the importance of refusing to be invisible and the need to create public queer spaces where GLBTIQ lives can be celebrated - particularly in regional areas.The shifting population demographics within the GLBTIQ communities in the Twenty-First Century needs to be carefully considered and respectfully represented in all spaces. Particularly, transgender communities internationally are increasing and require consultation and inclusion. The responsibility to create a culturally relevant, just and responsive society falls upon each one of us, whatever your specialist area. In sharing the story of Queer Fruits Film Festival, it is hoped that you can be inspired to create, to change, to grow in the 21st century with a broader understanding of the complex society in which we all live.